Effects of Copper(II) Complexes on the Growth of Escherchia coli by Microcalorimetry - Shen, Ping (Asian Journal of Chemistry, 2013)
Copper(II) complexes were synthesized and their effects on the growth of Escherchia coli (E. coli) were studied by microcalorimetry. Based on the power-time curves of Escherchia coli growth under the action of these copper(II) compounds, thermodynamics and kinetic data of metabolism of E. coli were calculated. The results revealed that there were differences in their capacities to inhibit the metabolism of this bacterium. The growth rate constant decreased with increasing concentrations of the copper complexes. Judged from the half-inhibitory concentration (IC50) [Cu(phen)2]Cl2·6H2O and [Cu(phen)3]Cl2·6H2O have the strongest antibacterial activity and CuCl2·2H2O has the weakest antibacterial activity.